When the subaltern speaks: Re-examining indigenous-language media as alternative public sphere during colonial South Africa. (1st June 2018) - Motsaathebe, Gilbert
This article attempts to examine the efficacy of indigenous-language newspapers published in South Africa during the colonial era. In doing so, the article is particularly interested to see how the success achieved by those publications could be replicated to boost post-apartheid indigenous-language media in their encounter with the hegemonic onslaught of the mainstream media whose scope and hegemony continue to expand at an alarming rate. The article embraces the notion of the public sphere and the theory of hegemony to make sense of how indigenous media permeated the language and political discourse and emerged as a strong voice for the oppressed, reinforcing at once what Herman and Chomsky (2002) refer to as 'class consciousness'. The notion of the public sphere is found to be particularly profitable in highlighting the exclusion/inclusion of wide-ranging voices in the public affairs while the robustness of the theory of hegemony lies in its strengths to unravel the political imperatives and the ideological contest that characterized the colonial era. The article argues that indigenous publications succeeded in becoming viable platforms for the indigenous communities who had been pushed beyond the margins of citizenship. The article concludes that indigenous-language media were particularly important for their political mobilization and contribution to media diversity through the range of voices that they orchestrated.